If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -5(3 + -1y) = 2 + -1(4 + -5y) 2 + (3 * -5 + -1y * -5) = 2 + -1(4 + -5y) 2 + (-15 + 5y) = 2 + -1(4 + -5y) Combine like terms: 2 + -15 = -13 -13 + 5y = 2 + -1(4 + -5y) -13 + 5y = 2 + (4 * -1 + -5y * -1) -13 + 5y = 2 + (-4 + 5y) Combine like terms: 2 + -4 = -2 -13 + 5y = -2 + 5y Add '-5y' to each side of the equation. -13 + 5y + -5y = -2 + 5y + -5y Combine like terms: 5y + -5y = 0 -13 + 0 = -2 + 5y + -5y -13 = -2 + 5y + -5y Combine like terms: 5y + -5y = 0 -13 = -2 + 0 -13 = -2 Solving -13 = -2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 48=2x-6 | | 1=5p-2-4p | | 4=7x | | 2(6-8x)=4(2x-3) | | -11x+22=45 | | r+0.27=-0.59 | | 6(-x-2)=48 | | r+0.27=-0.25 | | -7x+6=48 | | 2(x+1)=3(x+7)-12 | | 2x/3=6-x/4 | | 25x^2-129=0 | | 3(2+x)=2(2+x) | | x^3+10x^2+13x+24=0 | | 2(x+1)=3(x+7) | | x-2(6)=2 | | 3s^2=2s^2+1 | | 5x+4=-x-20 | | -10x-4x+13x=0-7 | | 5x-7(x-4)=51 | | 14x=(5x+14) | | y=xk | | .3.7(-83x-3)=3.7(7x-30) | | 3x+61=6x-11 | | 245-2x=43x+15 | | 5x-x=14*5 | | 6.7=-3.2+x | | 159-4x=23x+15 | | a=bc+d | | 96=5x^2-x^2 | | 41-7x=90 | | 1-5x-36x^2=0 |